2012
DOI: 10.1002/hpm.2141
|View full text |Cite
|
Sign up to set email alerts
|

Nigerian resident doctors on strike: insights from and policy implications of job satisfaction among resident doctors in a Nigerian teaching hospital

Abstract: To restore satisfaction and possibly stem industrial disputes by resident doctors, government of Nigeria needs to sustain current wages while introducing non-financial benefits. There is a need to adopt policies geared towards increasing government spending on health especially in the area of human capacity and infrastructural development, so as to afford resident doctors opportunities for skill acquisition and career development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…(e.g. [ 74 , 77 , 85 , 90 , 93 , 104 , 106 – 108 , 113 , 118 , 130 , 131 , 138 , 139 , 142 , 143 , 149 , 153 , 157 , 159 , 165 , 174 ]). These bundles are mainly linked to positive employee outcomes (e.g., improved job satisfaction, retention, and performance) and to a lesser extent to organizational outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…(e.g. [ 74 , 77 , 85 , 90 , 93 , 104 , 106 – 108 , 113 , 118 , 130 , 131 , 138 , 139 , 142 , 143 , 149 , 153 , 157 , 159 , 165 , 174 ]). These bundles are mainly linked to positive employee outcomes (e.g., improved job satisfaction, retention, and performance) and to a lesser extent to organizational outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…The focus of health service delivery should be on teamwork, rather than factional or individual strengths. Many have argued that this is perhaps the single most important factor in Nigeria, and until agreeable solutions are found across various professional groups, the Nigerian health system may continue to suffer from repeated and avoidable disruption of health service delivery [21]. …”
Section: Discussionmentioning
confidence: 99%
“…While these need to be addressed urgently, there is also the need to strategically adopt broader range of motivational factors [22]. Some authors have suggested that one basic way to address conflicts among health professionals and possibly stem industrial disputes is to introduce an evenly spread non-financial benefits to the health workforce [21]. This may be in form of career development, special skills acquisition and other varieties of human capacity development programmes.…”
Section: Discussionmentioning
confidence: 99%
“…The embitterment of not being treated equally by the government was de‐motivating. Other studies have also shown that such disparities have resulted in health workers migrating from state‐owned rural facilities to federal‐owned tertiary ones located in urban areas (Akinyemi and Atilola, ). Key informant interviews also confirmed that remuneration packages for the same cadre and grade of health worker differed by the type of facility, typically being higher for tertiary and secondary.…”
Section: Discussionmentioning
confidence: 99%